Functional Connectivity Is Altered in Concussed Adolescent Athletes Despite Medical Clearance to Return to Play: A Preliminary Report - Newsome, Mary R.; Li, Xiaoqi; Lin, Xiaodi; Wilde, Elisabeth A.; Ott, Summer; Biekman, Brian; Hunter, Jill V.; Dash, Pramod K.; Taylor, Brian A.; Levin, Harvey S. (Frontiers in Neurology, 2016)
Recovery following sports related concussion (SRC) is slower and often more complicated in young adolescent athletes than in collegiate players. Further, the clinical decision to return to play is currently based on symptoms and cognitive performance without direct knowledge of brain function. We tested the hypothesis that brain functional connectivity would be aberrant in recently concussed, asymptomatic athletes who had been cleared to return to play. A seed-based functional connectivity (FC) analysis measured the FC of the default mode network (DMN) (seeds = anterior cingulate cortex, posterior cingulate cortex, right lateral parietal cortex, and left lateral parietal cortex) 30 days after SRC in asymptomatic high school athletes cleared to return to play (n=13) and was compared to the FC of high school athletes with orthopedic injury (OI) (n=13). The SRC group demonstrated greater FC than the OI group between the posterior cingulate cortex and the ventral lateral prefrontal cortex, as well as between the right lateral parietal cortex and lateral temporal cortex (with regions both outside of and within the DMN). Additionally, the OI group demonstrated greater FC than the SRC group between right lateral parietal cortex and supramarginal gyrus. When relating the FC results to verbal memory performance approximately one week and one month after injury, significantly different between-group relations were found for the posterior cingulate and right lateral parietal cortex seeds. However, the groups did not differ in verbal memory at one month. We suggest that changes in FC are apparent one month post-SRC despite resolution of post-concussion symptoms and recovery of cognitive performance in adolescent athletes cleared to return to play.